The Effect of Fixed Exchange Rates on Monetary Policy - Shambaugh, J. C. (Quarterly Journal of Economics, 2004)
To investigate how a fixed exchange rate affects monetary policy, this paper classifies countries as pegged or non-pegged and examines whether a pegged country must follow the interest rate changes in the base country. Despite recent research which hints that all countries, not just pegged countries, lack monetary freedom, the evidence shows that pegs follow base country interest rates more than non-pegs. This study uses actual behavior, not declared status, for regime classification; expands the sample including base currencies other than the dollar; examines the impact of capital controls, as well as other control variables; considers the time series properties of the data carefully; and uses cointegration and other levels-relationship analysis to provide additional insights.